2021
DOI: 10.1016/j.isci.2021.102888
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A-induced DNA damages promote to lymphoma progression in human lymphoblastoid cells through aberrant CTNNB1 signaling pathway

Abstract: Highlights CTNNB1 is an initiator of BPA-mediated lymphomagenesis by gene-network analysis BPA exposure promotes clonogenic survival of damaged TK6 lymphoblastoid cells BPA/CTNNB1 dysregulates DNA-repairassociated genes TP53 and CDKN1A BPA-/CTNNB1-mediated lymphomagenesis is attributable to DNA breaks and G2/M arrest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…There is increasing concern that BPA perturbs the immune system causing adverse health effects including cancer [ 179 , 180 , 181 ]. It has recently been shown that BPA-induced DNA damages promote lymphoma progression in human lymphoblastoid cells through the aberrant catenin-β1 signaling pathway [ 37 ]. Gene-network analysis of microarray data sets in human lymphoma tissues as well as in human cells with BPA exposure to explore module genes identified potential pathways for lymphomagenesis in response to BPA [ 37 ].…”
Section: Potential Milk-related Factors Promoting Dlbclmentioning
confidence: 99%
See 3 more Smart Citations
“…There is increasing concern that BPA perturbs the immune system causing adverse health effects including cancer [ 179 , 180 , 181 ]. It has recently been shown that BPA-induced DNA damages promote lymphoma progression in human lymphoblastoid cells through the aberrant catenin-β1 signaling pathway [ 37 ]. Gene-network analysis of microarray data sets in human lymphoma tissues as well as in human cells with BPA exposure to explore module genes identified potential pathways for lymphomagenesis in response to BPA [ 37 ].…”
Section: Potential Milk-related Factors Promoting Dlbclmentioning
confidence: 99%
“…It has recently been shown that BPA-induced DNA damages promote lymphoma progression in human lymphoblastoid cells through the aberrant catenin-β1 signaling pathway [ 37 ]. Gene-network analysis of microarray data sets in human lymphoma tissues as well as in human cells with BPA exposure to explore module genes identified potential pathways for lymphomagenesis in response to BPA [ 37 ]. BPA exposure resulted in a disrupted cell cycle and DNA damage by activating catenin-β1 encoded on the catenin-β1 gene ( CTNNB1 ), the initiator of the aberrant constructed CTNNB1-NFKB1-AR-IGF-1-TWIST1 pathway, which may potentially lead to lymphomagenesis [ 37 ].…”
Section: Potential Milk-related Factors Promoting Dlbclmentioning
confidence: 99%
See 2 more Smart Citations
“…BPA exposure has been described to result in disrupted cell cycle and DNA damage by activating Catenin Beta 1 (CTNNB1), which is the initiator of the aberrant constructed CTNNB1-nuclear factor kappa-B1 (NFKB1)-AR-insulin-like growth factor-1 (IGF1)-Twist-related protein 1 (TWIST1) pathway, potentially leading to lymphomagenesis [ 76 ].…”
Section: Bisphenol a Effects On Human Healthmentioning
confidence: 99%